2012
DOI: 10.1038/ncomms1915
|View full text |Cite
|
Sign up to set email alerts
|

Histone modifications and lamin A regulate chromatin protein dynamics in early embryonic stem cell differentiation

Abstract: Embryonic stem cells are characterized by unique epigenetic features including decondensed chromatin and hyperdynamic association of chromatin proteins with chromatin. Here we investigate the potential mechanisms that regulate chromatin plasticity in embryonic stem cells. Using epigenetic drugs and mutant embryonic stem cells lacking various chromatin proteins, we find that histone acetylation, G9a-mediated histone H3 lysine 9 (H3K9) methylation and lamin A expression, all affect chromatin protein dynamics. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
137
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 58 publications
6
137
0
1
Order By: Relevance
“…Consistent with this function, histone acetylation is highly enriched in ESCs compared with differentiated cells [19,20,25,26], indicating that it contributes to the open chromatin state in ESCs. Consistently, treatments of HDAC inhibitors have been shown to enhance nuclear dynamics, reduce differentiation propensity [46] and support the selfrenewal program in ESCs [47]. In addition, in cell fusion-mediated reprogramming, low levels of histone H3 K9 acetylation (H3K9ac) in ESCs correlate with reduced efficiency in reprogramming the nuclei from fibroblasts, and HDAC inhibitors can improve the reprogramming efficiency [48].…”
Section: Histone Acetylationmentioning
confidence: 90%
See 1 more Smart Citation
“…Consistent with this function, histone acetylation is highly enriched in ESCs compared with differentiated cells [19,20,25,26], indicating that it contributes to the open chromatin state in ESCs. Consistently, treatments of HDAC inhibitors have been shown to enhance nuclear dynamics, reduce differentiation propensity [46] and support the selfrenewal program in ESCs [47]. In addition, in cell fusion-mediated reprogramming, low levels of histone H3 K9 acetylation (H3K9ac) in ESCs correlate with reduced efficiency in reprogramming the nuclei from fibroblasts, and HDAC inhibitors can improve the reprogramming efficiency [48].…”
Section: Histone Acetylationmentioning
confidence: 90%
“…*Enhanced effi- [197]; defect in neur- [197] ciency by Kmt1c oectoderm contribution inhibitor [73] in teratoma [46] Kmt1d/ NA Reduced NA NA Postimplantation Ehmt1/ efficiency [74] lethality (E8.5-9.5) Glp1 [197] Kmt1e/ NA Reduced Failure and acquiIncorporation to trophe-Peri-implantation Eset/ efficiency [74] sition of trophectctoderm upon blastocyst lethality (E3.5-5.5) the requirement growth rate [122] of Klf4 [74] [122]…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have shown that patterns of histone modification have been associated with many essential biological processes, such as stem cell maintenance and differentiation. 10,16,21 Previous studies have revealed that mesenchymal stem cells exist in ligamentum flavum and play a crucial role in the development of OLF. 3,18 Whether histone modifications are involved in this ossification process has not been studied.…”
mentioning
confidence: 99%
“…Since Lamin A/C has very low expression in ESCs, it has been suggested as a marker of differentiation. 23 The nuclei of hESCs are more deformable than their differentiated counterparts. Pajerowski et al used microaspiration to determine that the nuclei of hESCs stiffen by as much as sixfold as they reach terminal differentiation.…”
Section: Mechanical Properties Of Hpscsmentioning
confidence: 99%